2008
DOI: 10.1007/s11999-008-0351-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results With a Lateral Unicondylar Replacement

Abstract: While the literature suggests lateral unicondylar knee arthroplasty (UKA) improves function in the shortand medium-term, it is less clear on longer-term function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
1
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 29 publications
(87 reference statements)
2
80
1
9
Order By: Relevance
“…Long-term results after 13 yearshave showedsurvivorships of greater than 90% [21]. Repeated clinical and radiographic follow-up confirmed a reduction in pain and an increase in function and range-of-motion components in patients after lateral UKA after 60 months [22].…”
Section: Discussionmentioning
confidence: 82%
“…Long-term results after 13 yearshave showedsurvivorships of greater than 90% [21]. Repeated clinical and radiographic follow-up confirmed a reduction in pain and an increase in function and range-of-motion components in patients after lateral UKA after 60 months [22].…”
Section: Discussionmentioning
confidence: 82%
“…While many studies describe MUKA, there are far fewer studies describing pain relief and restoration of function after LUKA [4,7,9,18,22,29,33,34,36,39,41]. Even when the procedure is reported in the literature, the numbers in the studies are small and the surgical approach is either via a medial parapatellar, not described, or rarely described as being via the lateral parapatellar [36].…”
Section: Discussionmentioning
confidence: 99%
“…In the series with perhaps the longest followup, O'Rourke et al [33] noted 72% survival in 14 LUKAs at 24 years. In recent studies with fixed-bearing, cemented tibial implants, Argenson et al [7] reported a prosthesis survivorship of 92% at 10 years and 84% at 16 years. Sah and Scott [39] described LUKA through a median parapatellar arthrotomy in 49 patients and observed no revisions at 5.4 years postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations